Enhancing mitochondrial activity in neurons protects against neurodegeneration in a mouse model of multiple sclerosis - Rosenkranz, Sina Cathérine; Shaposhnykov, Artem A; Träger, Simone; Engler, Jan Broder; Witte, Maarten E; Roth, Vanessa; Vieira, Vanessa; Paauw, Nanne; Bauer, Simone; Schwencke-Westphal, Celina; Schubert, Charlotte; Bal, Lukas Can; et al. (eLife, 2021)
While transcripts of neuronal mitochondrial genes are strongly suppressed in central nervous system inflammation, it is unknown whether this results in mitochondrial dysfunction and whether an increase of mitochondrial function can rescue neurodegeneration. Here, we show that predominantly genes of the electron transport chain are suppressed in inflamed mouse neurons, resulting in impaired mitochondrial complex IV activity. This was associated with post-translational inactivation of the transcriptional co-regulator proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α). In mice, neuronal overexpression of Ppargc1a, which encodes for PGC-1α, led to increased numbers of mitochondria, complex IV activity, and maximum respiratory capacity. Moreover, Ppargc1a-overexpressing neurons showed a higher mitochondrial membrane potential that related to an improved calcium buffering capacity. Accordingly, neuronal deletion of Ppargc1a aggravated neurodegeneration during experimental autoimmune encephalomyelitis, while neuronal overexpression of Ppargc1a ameliorated it. Our study provides systemic insights into mitochondrial dysfunction in neurons during inflammation and commends elevation of mitochondrial activity as a promising neuroprotective strategy.